Tingkat Bagi Hasil Deposito Melalui Variabel Intervening Dana Pihak Ketiga Terhadap Pembiayaan Mudharabah Bank Syariah - Setiyo Aji; Imron Mawardi (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This study aims to determine the effect of profit sharing rates on deposits to third party funds and financing mudharabah sharia banks partially or simultaneously. The approach used is a quantitative approach by using the pathway analysis technique with three variables, namely the profit-sharing rate of deposits as ecogenous variable. Population in this study is the sharia bank industry registered in the statistics of Islamic banking published by the website of the Bank Indonesia. The sample used in this study as many as 60 samples with data from January 2012 until December 2016. Data collection is done by collecting financial statements of the sharia bank industry monthly period 2012-2016.Keywords: Sharia banks, profit-sharing rates, third party funds, mudharabah financingREFFERENCESAntonio, M. S. (2001). Bank Syariah: Dari teori Ke Praktik . Jakarta: Gema Insani Press.Anjani, R., & Hasmarani, M. I. (2016). Pengaruh Pembiayaan Mudharabah, Musyarakah Dan Murabahah Terhadap Profitabilitas BPRS Di Indonesia Periode 2012-2015.Syariah Paper Accounting FEB UMS.Arifin, Z. (2009). Dasar-dasar Manajemen Bank Syariah. Tangerang: Azkia Publisher.Arnan dan Kurniawasih. (2014). Pengaruh Jumlah Dana Pihak Ketiga dan Tingkat Non-Performing Financing Terhadap Pembiayaan Mudharabah pada Bank Umum Syariah di Indonesia.Proceedings SNEB 2014: 2.Aswad. (2014). Analisis Bagi Hasil Financing dalam Perbankan Syariah. Vol. 1, No. 1, Oktober 2014.Bahri. (2015). Model Penelitian Kuantitatif Berbasis SEM-Amos. Yogyakarta: DeepublishBarus, A. C., & Sulistyo, D, (2011), Hubungan Efisiensi Operasional Dengan Kinerja Profitabilitas Pada Sektor Perbankan Yang Go Public Di Bursa Efek Indonesia.Jurnal Wira Ekonomi Mikroskil, Vol. 1, No. 02, hal 89-97.Chair, W. 2014.Riba Dalam Perspektif Islam.Iqtishadia Vol. 1 No. 1Daniar. 2015. Asuransi Perspektif Al-Qur’an. Islamic Economic JournalVol. 1, No. 2 ISSN 2460-1896Fadhila, N. (2015). Analisis Pembiayaan Mudharabah Dan Murabahah Terhadap Laba Bank Syariah Mandiri.Jurnal Riset Akuntansi Dan Bisnis, Vol. 15, No. 1.Fahrul, F., Arfan, M., & Darwanis. (2012). Pengaruh Tingkat Risiko Pembiayaan Musyarakah Dan Pembiayaan Murabahah Terhadap Tingkat Profitabilitas Bank Syariah (Studi Pada Bank Aceh Syariah Cabang Banda Aceh). Jurnal Akuntansi Pascasarjana Universitas Syiah Kuala, Vol. 2, No. 1.Ferdiansyah. (2015). Pengaruh Rate Bagi Hasil Dan BI Rate Terhadap Dana Pihak Ketiga Perbankan Syariah (Studi Pada Bank Pembiayaan Rakyat Syariah Yang Terdaftar Di Bank Indonesia).JOM Fekon, Vol. 2, No. 1.Gani, I., & Amalia, S. 2015.Alat Analisis Data: Aplikasi Statistik untuk Penelituan Bidang Ekonomi dan Sosial. Yogyakarta: Andi.Ghazali, I. 2011. Model Persamaan Struktural Konsep dan Aplikasi dengan Program Amos 19,0. Semarang: UndipGustina, 2011. Islamic Banking System: Studi Analisis Perkembangan Perbankan Syariah Di Indonesia.Jurnal Akuntansi & Manajemen Vol 6 No.1 ISSN 1858-3687Hadad, M. D. 2017. Laporan Perkembangan Keuangan Syariah 2016. OJK (Otoritas jasa keuangan)